The interaction between dietary crude protein and amino acid levels in weaner pigs in an antibiotic-free environment with or without Bacillus amyloliquefaciens supplementation - Jansen van Rensburg, Christine (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.